PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Hasyim As’ari (Delta: Jurnal Ilmiah Pendidikan Matematika, 2019)
Prospective math teachers should be able to master basic skills in doing math problems. One of the skills in doing mathematics is the ability to solve math problems. However, in fact students of Mathematics Education Study Program of Pekalongan University Semester 4 as math teacher candidate is still lacking in problem solving ability. Besides iu, teaching materials that contain mathematical problem solving strategies are also not available so in learning the problem-solving ability is still lacking.In this study developed a problem-based mathematics learning module in which contains problem-solving strategies. This research aims to: 1) acquire and describe modules that fit the needs of the 4th semester students of Mathematics Education, 2) produce mathematical problem solving modules, 3) produce appropriate problem-based math learning modules and 4) produce effective modules to improve capability mathematical problem solving on semester 4 students. This development research using the development model Thiagarajan et al. The steps undertaken in this research and development are defining, designing and developing.Based on the result of the research, the description and design of the module according to the problems of the students of Mathematics semester 4. Meanwhile, the total aspect of all validator is 4.175. According to the validation criteria makka can be concluded that the developed learning module included in the category valid. This means that the developed learning media is valid. Meanwhile, based on the test in the afternoon class, obtained some input which is then refined to then be used in trials in the morning class students. Based on pre test and post test results, both data were analyzed using wilcoxon test yielding Zobs of -3.399. Based on the right-side test criteria, the result of the decision is that the average post test score is higher than the average pre test value. This means that the modules are developed effectively for use in Mathematics Education students semester 4.